2023
DOI: 10.3390/s23031735
|View full text |Cite
|
Sign up to set email alerts
|

Multiple In-Mold Sensors for Quality and Process Control in Injection Molding

Abstract: The simultaneous improvement of injection molding process efficiency and product quality, as required by Industry 4.0, is a complex, non-trivial task that requires a comprehensive approach, which involves a combination of sensoring and information techniques. In this study, we investigated the suitability of in-mold pressure sensors to control the injection molding process in multi-cavity molds. We have conducted several experiments to show how to optimize the clamping force, switchover, or holding time by mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Xu et al [ 13 ] proposed a method based on the variation in clamping force to determine the optimal clamping force, showing that the optimal setting for the clamping force could be found when the clamping force variation was zero. Párizs et al [ 14 ] proposed the feasibility of controlling the injection process using cavity pressure sensors in multi-cavity molds, reporting that the sensors could effectively detect the filling end time to determine the appropriate V / P switchover point, fit the pressure curve to determine the proper filling time, and analyze the pressure curve and pressure integral to determine the suitable clamping force. Huang et al [ 15 ] found that setting the V / P switchover point too early or too late would significantly impact the cavity pressure curve and product quality.…”
Section: Introductionmentioning
confidence: 99%
“…Xu et al [ 13 ] proposed a method based on the variation in clamping force to determine the optimal clamping force, showing that the optimal setting for the clamping force could be found when the clamping force variation was zero. Párizs et al [ 14 ] proposed the feasibility of controlling the injection process using cavity pressure sensors in multi-cavity molds, reporting that the sensors could effectively detect the filling end time to determine the appropriate V / P switchover point, fit the pressure curve to determine the proper filling time, and analyze the pressure curve and pressure integral to determine the suitable clamping force. Huang et al [ 15 ] found that setting the V / P switchover point too early or too late would significantly impact the cavity pressure curve and product quality.…”
Section: Introductionmentioning
confidence: 99%
“…The final properties of a plastic part are greatly affected by the production parameters. The best way to control the process is to use sensors in the mold [4,5]. In case of injection molding, melt temperature, mold temperature, injection rate, holding time, and holding pressure significantly affect the properties of injection molded parts [6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…There is much interest in the framework of Industry 4.0 in providing feedback during the injection moulding process. The current work on operando SAXS measurements provides one approach to providing feedback on multiple scales, but the role of more traditional "sensors" should not be overlooked, and reference [22] gives an excellent coverage of such possibilities.…”
Section: Introductionmentioning
confidence: 99%